Research on the threshold effect of population aging on the industrial structure upgrading in China. Issue 1 (2nd January 2019) - Liu, Chengkun; Li, Shuyu; Zhao, Xindong
ABSTRACT: This paper constructs coefficients of the integral and the internal structure upgrading in the secondary and tertiary industries, selects per capita real gross domestic product as a threshold variable and build panel threshold model according to inter-provincial panel data of China from 1998 to 2016. Results indicated that population aging has a double threshold effect on the integral industrial structure upgrading, whose influence increases first and then decreases, significantly promoting the upgrading process. As for internal structure, population aging has no significant threshold effect on the upgrading in the secondary industry, but exerts a single negative threshold effect in the tertiary industry. When economic development is under the threshold, its negative impact is greater. Further analysis also suggests that regional differences exist significantly in the threshold effect of population aging on the industrial structure upgrading.